SMART FISH DRYING: Solar-powered Automatic Salted Fish Production System - Arini, Nadine Nova; Bisri, Shahwa Namira; Jaenuri, Jaenuri; Farahdina, Ulya (Jurnal Penelitian Sains, 2025)
Due to weather instability in recent years, dried fish production in Indonesia has declined, while the quality of the produced dried fish remains low. To address this challenge, the authors introduce "SMART FISH DRYING," an automatic fish drying system based on a transparent greenhouse structure. This system uses acrylic walls and a convex lens roof that focuses sunlight. Inside "SMART FISH DRYING," fish are arranged on a stainless steel wire mesh table equipped with a humidity sensor that automatically rotates the table when the fish's moisture content on one side reaches 30%. When both sides reach the desired moisture level, an LED light and alarm activate, signaling that the dried fish is ready for harvesting. "SMART FISH DRYING" operates using solar cells connected to a battery, significantly reducing energy consumption and operational costs. Additionally, the system features a gas collection system to capture H?S compounds released during the drying process, which can be processed into pesticides. This process is monitored by an MQ136 gas sensor to measure the concentration of harmful compounds. Moreover, "SMART FISH DRYING" optimizes the moisture from the drying process through a distillation system to produce purified water as a byproduct. With this technology, dried fish production can be accelerated by two times compared to traditional methods, with a fourfold increase in profitability and a 20% improvement in product quality.Keywords: dried fish; convex lens; automatic; solar.